BnTIR: an online transcriptome platform for exploring RNA‐seq libraries for oil crop Brassica napus - Liu, Dongxu; Yu, Liangqian; Wei, Lulu; Yu, Pugang; Wang, Jing; Zhao, Hu; Zhang, Yuting; Zhang, Shuntai; Yang, Zhiquan; Chen, Guanqun; Yao, Xuan; Yang, Yanjun; et al. (Plant biotechnology journal, 2021)
To investigate the dynamic gene expression during B. napus development and provide an easy access visualization of the expression levels of B. napus genes, we performed RNA-seq for 91 different tissue samples including root, seedling, stem, 1st-23rd leaves from the main branch, flower buds (2 and 4 mm), flower tissues (sepal, petal, filament, and pollen), silique walls (2–60 day after flowering (DAF), with 2-day intervals) and seeds (14–64 DAF, with 2-day intervals) (Figure 1a). BnTIR is a refined transcriptome platform for Brassica napus. (a) Summary of statistics for transcriptome sequencing of diverse tissue types of B. napus. (b) The homepage of BnTIR. (c) Architecture of BnTIR database, including data source layer, middleware layer, and application layer. (d) eFP viewer. (e) Tissue expression viewer. (f) Co-expression viewer. (g) JBrower viewer. (h) Blast module. (i) Gene index module. (j) Sequence fetch module. (k) Transcription factor module. (l–o) A case of application of BnTIR, including the phylogenetic tree and expression profile of BAN and their four B. napus homolog genes (l); expression comparison of B. napus BAN homolog genes in seed and silique wall (m); the co-expression network of homolog genes of BAN (n); and expression profile of co-expressed genes of BAN (o). According to PlantTFDB, the information of 58 TF families in B. napus is also provided in the tool interface (Figure 1k; http://planttfdb.gao-lab.org/).